Kreatywność jako podstawowa cecha zarządzania małym i średnim przedsiębiorstwem - Sudoł, Tomasz (Creativity as an essential feature of managing a small and a medium-size enterprise, 2005)
The author analyses the first phase of organization growth according to Greiner, i.e. the creativity stage, adjusting Greiner's assumptions to Polish conditions. In the article there is also an analysis of preparations of companies to transition from the creativity stage to the stage of directions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 528-532